Identification of Novel Parishin Compounds from the Twig of Maclura tricuspidata and Comparative Analysis of Parishin Derivatives in Different Parts - Dae-Woon Kim; Jong-Kuk Kim; Yoseph Asmelash Gebru; Young-Hoi Kim; Han-Seok Choi; Myung-Kon Kim (Molecules, 2022)
Parishin compounds are rare polyphenolic glucosides mainly found in the rhizome of the traditional Chinese medicinal plant, Gastrodia elata. These constituents are reported to have several biological and pharmacological activities. In the present study, two novel parishin derivatives not previously reported as plant-based phytochemicals were identified from a twig of Maclura tricuspidata (MT) and two new compounds were elucidated as 1-(4-(β-d-glucopyranosyloxy)benzyl)-3-hydroxy-3-methylpentane-1,5-dioate (named macluraparishin E) and 1,3-bis(4-(β-d-glucopyranosyloxy)benzyl)-3-hydroxy-3-methylpentane- 1,5-dioate (macluraparishin C), based on the experimental data obtained by UV–Visible (UV–Vis) spectroscopy, high performance liquid chromatography–quadrupole time-of-flight mass spectrometry (HPLC-QTOF-MS) and nuclear magnetic resonance (NMR) spectroscopy. Additionally, gastrodin, parishin A and parishin B were positively identified by spectroscopic evidence and the comparison of HPLC retention time with the corresponding authentic standards. Gastrodin, parishin A and parishin B, macluraparishin E and macluraparishin C were found to be the most abundant constituents in the MT twig. The compositions and contents of these constituents were found to vary depending on the different parts of the MT plant. In particular, the contents of parishin A, parishin B, macluraparishin C and macluraparishin E were higher in the twig, bark and root than in the leaves, xylem and fruit.